2015
DOI: 10.1021/jacs.5b10856
|View full text |Cite
|
Sign up to set email alerts
|

Hole Transfer from Photoexcited Quantum Dots: The Relationship between Driving Force and Rate

Abstract: We have investigated the relationship between driving force and rate for interfacial hole transfer from quantum dots (QDs). This relationship is experimentally explored by using six distinct molecular hole acceptors with an 800 meV range in driving force. Specifically, we have investigated ferrocene derivatives with alkyl thiol moieties that strongly bind to the surface of cadmium chalcogenide QDs. The redox potentials of these ligands are controlled by functionalization of the cyclopentadiene rings on ferroce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
168
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(176 citation statements)
references
References 53 publications
8
168
0
Order By: Relevance
“…A high specific area would increase not only the number of active catalytic sites, but also the number of superficial defect sites, which promote the recombination of free charge carriers [139]. For example, it has been reported that a high surface area for metal chalcogenides promotes the recombination processes through a "non-radiative" decay [140]. On the contrary, other studies demonstrated that an increase in the surface area of nanostructured titania does not generate an enhancement of the recombination rate of photogenerated charges [141].…”
Section: Surfacementioning
confidence: 99%
“…A high specific area would increase not only the number of active catalytic sites, but also the number of superficial defect sites, which promote the recombination of free charge carriers [139]. For example, it has been reported that a high surface area for metal chalcogenides promotes the recombination processes through a "non-radiative" decay [140]. On the contrary, other studies demonstrated that an increase in the surface area of nanostructured titania does not generate an enhancement of the recombination rate of photogenerated charges [141].…”
Section: Surfacementioning
confidence: 99%
“…[19][20] Furthermore, as recently discovered, the enhancement of Auger interactions in surface charged QDs causes non-Marcus behavior in charge-transfer processes. 15,[21][22] Depending on the application, all these photo-physical processes can be either useful or detrimental. A rational development of nanostructures, with tailored trapping, is crucial in view of their practical application.…”
Section: Introductionmentioning
confidence: 99%
“…F TET(TA) was extracted from the kinetics at 445 nm of the CdSe/PyAn complexes after accounting for the contribution of the NC (Figure 3; see also Figure S8). [7,20] Another way of calculating the quantum efficiency of TET is by considering the photon upconversion QY obtained under CW irradiation, which is aconvolution of the following factors in Equation (3). In addition, the 2,2-PyAn transmitter with the lowest upconversion QY has the lowest F TET(TA) .H owever, we noticed that 2,2-PyAn quenches the CdSe NC donor more effectively than the 3,3-PyAn isomer (Figure 2c and Table 1) despite the fact that it has alower F TET(TA) and upconversion QY.T his observation is consistent with reports on the superlinear dependence of NC emission on ligand functionalization, and that NC photoluminescence can only be related to ligand binding at high surface coverage,and not at the low density of transmitter ligands in this work.…”
Section: Angewandte Chemiementioning
confidence: 99%